Pengaruh Harga, Kualitas Pelayanan, dan Kepuasan Pelanggan terhadap Loyalitas Pelanggan pada Klinik Umum Nur Hikmah Sehat - Dede Hertina; Andya Fitrist Bani Koni (J-MAS (Jurnal Manajemen dan Sains), 2023)
The purpose of this study was to analyze the effect of service quality and customer satisfaction on customer loyalty. This research was conducted at the Nur Hikmah Sehat clinic located on Margacinta Street Bandung. This research technique uses quantitative methods with questionaire survey techniques. The population of this study was 65 people, with a sample size of 60 people. The results of the study simultaneously state that Price, Service Quality and Customer Satisfaction have a significant effect on Customer Loyalty at the Nur Hikmah Sehat Clinic. While the partial research results state that Price and Customer Satisfaction have an effect on Loyalty. Service quality has a positive effect on Customer Loyalty.